Stress Moderates the Effect of Childhood Trauma and Adversity on Recent Drinking in Treatment-seeking Alcohol-dependent Men - Eames, Sarah F. (2014)
OBJECTIVE: This study sought to clarify the relationship between childhood trauma and adversity with later alcohol consumption and the moderating effects of adult psychosocial stress. METHOD: Seventy-seven recently abstinent alcohol-dependent men attending residential treatment programs were assessed. Childhood trauma/adversity was assessed with the Childhood Trauma Questionnaire (CTQ), drinks per drinking day (DDD) with the TimeLine Follow Back, and chronic psychosocial stress with the UCLA Stress Interview. Drinking and stress were retrospectively assessed for six months prior to the present treatment episode. Direct associations between childhood trauma/adversity and alcohol consumption and the moderating effects of recent psychosocial stress were assessed. All measures were considered as continuous variables. RESULTS: Pretreatment drinking severity (DDD) was associated with CTQ Total score (p = .009) and the Emotional Abuse (p < .001) and Physical Abuse (p < .01) subscales. UCLA Total Stress significantly moderated the effects of CTQ Total score on drinking severity (p = .04). Whereas higher CTQ scores were significantly associated with a greater amount of pretreatment drinking in participants with high UCLA stress scores (p = .01), CTQ scores were not associated with the amount of drinking in those with low UCLA stress scores (p = .63). CONCLUSIONS: Childhood trauma predicts drinking severity in alcohol-dependent men and this effect is stronger in participants with ongoing stress in adult life. These findings suggest that early childhood trauma/adversity may sensitize stress-response systems.